ASSESSMENT OF GROUNDWATER RESOURCES FOR IRRIGATION PURPOSES IN ASSIUT GOVERNORATE, UPPER EGYPT - Mamdouh, S. Morsi; Farrag, Abdelhai A.; Sayed, Esam E. A. El (International Journal of Research -GRANTHAALAYAH, 2018)
A general increase of water demand in Egypt is prominently denoted. This situation is more noticeable in the Middle and Upper Egypt of arid Zone and limited water resources in which Assiut is one of the governorates of this Zone. The main objectives of this study are to assess the groundwater quality for irrigation, and to present solutions for managing and protecting these resources in Assiut area. To achieve that, one hundred and nine groundwater samples were collected from Quaternary aquifer during autumn of the year 2013. Chemical analysis was carried out and analyzed for major and trace elements according to the irrigation water guidelines of (FAO, 1985), and Rowe, et al. 1995, taking into account the spatial variations and the representation of the hydrochemical data. The results show that 47% none degree of restriction on use and 52% Slightly to moderate degree of restriction on use, According TDS hazarded. 55 % belongs to (C2-S1) good water for irrigation all crops in all soils and45 % belongs to (C3 -S1) good water for irrigation all crops in all soils under ordinary and specific condition like adequate drainage and leaching, According U.S. salinity laboratory staff classification depend on (EC,TDS and SAR) hazarded. while according to RSC (residual sodium carbonate100% Low RSC hazard (safe water for irrigation. 89% Excellent water for irrigation sensitive all crops and low likelihood of soil problems and11% good to permissible for irrigation semi - tolerant and tolerant crops and slightly to moderate likelihood of soil problems according Boron content, in compared to recommended limits in (FAO, 1995, 2010) guideline for irrigation water. Consequently, it is recommended to prevent the sewage and domestic waste water, and the industrial waste water from direct disposal without treatment to the ground wells, irrigation canals and River Nile; avoiding the construction of open septic tanks, especially near the pumping wells; controlling the use of fertilizers and pesticides in the agriculture purposes; selected the suitable crops for every sector (area) according to the chemical character’s of the available irrigation water and soil properties.